Counter-monuments: the anti-monumental and the dialogic. Issue 5 (4th July 2018) - Stevens, Quentin; Franck, Karen A.; Fazakerley, Ruth
Abstract : In recent decades, counter-monuments have emerged as a new, critical mode of commemorative practice. Even as such practice defines itself by its opposition to traditional monumentality, it has helped to reinvigorate public and professional interest in commemorative activities and landscapes and has developed its own, new conventions. Terminology and analysis in scholarship on counter-monuments have remained relatively imprecise with writers in English and German employing the term 'counter-monument' or Gegendenkmal in different and sometimes confusing ways. In this paper we draw together literature published in English and German to clarify and to map various conceptions and categorisations. To do so we distinguish between two kinds of projects that have been called counter-monuments: those that adopt anti-monumental strategies, counter to traditional monument principles, and those that are designed to counter a specific existing monument and the values it represents.